1990
DOI: 10.1139/y90-070
|View full text |Cite
|
Sign up to set email alerts
|

Increased sympathetic innervation in the cerebral and mesenteric arteries of hypertensive rats

Abstract: The density of catecholamine-containing nerve fibers was studied in the cerebral and mesenteric arteries from normotensive Wistar-Kyoto rats (WKY), spontaneously hypertensive rats (SHR), and stroke-prone SHR (SHRSP) in the growing (SHR, WKY) and adult (SHR, SHRSP, WKY) animals. Cerebral arteries from SHR showed an increased adrenergic innervation from day 1. The nerve plexuses reached an adult pattern earlier in SHR than in WKY. The arteries from adult SHR and SHRSP (22 weeks old) showed a markedly higher nerv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(13 citation statements)
references
References 0 publications
0
12
1
Order By: Relevance
“…Numerous studies have shown that increased sympathetic activity plays a role in the pathogenesis of hypertension [16,21,22]. Our results show that neither NA release nor the vasoconstrictor response to exogenous NA was modified by hypertension in female rats.…”
Section: Discussioncontrasting
confidence: 62%
“…Numerous studies have shown that increased sympathetic activity plays a role in the pathogenesis of hypertension [16,21,22]. Our results show that neither NA release nor the vasoconstrictor response to exogenous NA was modified by hypertension in female rats.…”
Section: Discussioncontrasting
confidence: 62%
“…In these rats, the levels of All are normal [35] while arteries are hyperinnervated [36,37], Besides neonatal sympathectomy [38], inhibitors of angiotensin-converting enzyme prevent small artery hypertrophy by a pressure-independent mechanism [31]. In general, experiments involving local surgical and systemic chemical or immunosympathectomy have indicated that sympathetic nerves exert a trophic influence in the young and stabilize arterial smooth mus cle cell contractile phenotype in the adult [39].…”
Section: Other Types O F Arteriesmentioning
confidence: 99%
“…These findings are in contrast to the enhanced tissue NA and enhanced sympathetic constrictor responses to EFS observed in tail arteries in the same DPSPX model of hypertension (Karoon et al, 1995). In the mesenteric vasculature of SHR there are conflicting reports of no change in the release of endogenous NA (Cline & Yamamoto, 1987) and elevated tissue NA and NPY content and augmented sympathetic neurotransmission (Scott & Pang, 1989;Longhurst et al, 1986;Lee et al, 1988;Heat, 1989;Mangiarua & Lee, 1989). Augmented sympathetic activity is a feature of other experimental models of hypertension and elevated plasma levels of NA have been reported in some patients with essential hypertension (De Champlain, 1990).…”
Section: Discussionmentioning
confidence: 88%